Smallholder agriculture in Ghana - Chamberlin, Jordan; Diao, Xinshen; Kolavalli, Shashidhara; Breisinger, Clemens (International Food Policy Research Institute, 2007)
In recent years, agricultural growth in Ghana has been positive overall. However, much of this growth has resulted from area expansion rather than increased yield. Furthermore, growth patterns have not been uniform across commodities or geographic regions. To increase agricultural performance, it is essential to target the small farmers who constitute the largest segment of producers. Policy objectives should aim to improve the delivery of services to smallholders and to develop new ways to include smallholders in more efficient value chains.